In Search of Self-Knowledge (Intertext of I. Brodsky’s Poem “The Procession”) - O. V. Bogdanova; E. A. Vlasova (Научный диалог)
In the article, based on the material of the “mystery poem” by I. Brodsky “The Procession” (1961), intertextual links are traced that allow us to penetrate into the deep layers of the poem, to see behind its plot not the story of a love disappointment (I. Romanova) or the motives of the farcical comedy dell’arte (E. Fetisova), but philosophical reflections on time, on life and death (life-death). The intertextuality in “The Procession” goes beyond literature: the compositional structure of the poem is mediated by the influence of jazz variations and blues repetitions. As a musical pretext of “The Procession”, the classic of the Leningrad dixieland “When the saints go marching in...” is attributed. According to the jazz harmony the plot of the poem is formed as a series of zongs-voices, variants-improvisations of Hamlet’s theme “To be or not to be?” (“life / death”), which in Brodsky’s poem received a subjective version: “death comes as if for the first time...” The “vortex” composition, mediated by the rhythms of jazz, allows Brodsky to lead the hero through all the circles of Dante’s “Hell”, bringing him closer to “Purgatory” in the final poem and giving him the opportunity to pass initiation, to be among the “initiates”. The hero does not reach the heights of “Paradise”, but he is granted “even breath [verse]”, explicating the idea of an eternal life march to an unattainable world harmony.